Egypt’s Takaful Cash Transfer Program: Impacts and recommendations from the second round evaluation - El-Enbaby, Hoda; Elsabbagh, Dalia; Gilligan, Daniel O.; Karachiwalla, Naureen; Kolt, Bastien; Kurdi, Sikandra (International Food Policy Research Institute, 2023)
Egypt’s national cash transfer program, Takaful, and its sister program Karama covered 17 million poor beneficiaries as of 2022, about 16 percent of the Egyptian population. Takaful was designed in 2015 as a conditional cash transfer program providing income support targeted to the most vulnerable, namely poor families with children under age 18. As one of the largest programs — both in absolute terms and in terms of share of the population covered — in the wave of national cash transfer programs spreading across Africa, as well as an innovator among countries in the Middle East, Egypt’s experience has the potential to serve as a model for these regions. The International Food Policy Research Institute (IFPRI), in collaboration with the Ministry of Social Solidarity, conducted a first-round evaluation of the program in 2017 to estimate its effects on household well-being (Breisinger et al. 2018). That evaluation found large positive impacts on several outcomes, most notably, household consumption. The second-round evaluation, conducted in 2022, found a shift toward greater investment in physical and human capital among program beneficiaries. This brief summarizes the main findings from that second-round evaluation, noting differences from the first evaluation results and providing key recommendations.